Shield synchronous grouting admixture, shield synchronous grouting material and preparation method of shield synchronous grouting material
By using independently developed shield synchronous grouting admixtures in shield synchronous grouting materials, the problem of poor water dispersion resistance of grouting materials in the prior art is solved, and an efficient and economical grouting effect is achieved, which significantly reduces material costs and construction periods.
Patent Information
- Application Number
- CN202411627395.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-28
AI Technical Summary
The existing shield synchronous grouting material has poor water dispersion resistance in a water-rich environment, resulting in deformation, layering or cracking of the grouting layer, and secondary grouting is required to increase material cost and construction period.
The independently developed shield synchronous grouting admixture is adopted, including polycarboxylic acid water reducer, polyacrylamide, sodium silicate, expansion agent and fly ash, and the performance of shield synchronous grouting material is optimized through the synchronous action of each component.
The high water dispersion resistance, appropriate consistency, rapid solidification and low shrinkage of shield synchronous grouting material are achieved. The expected secondary grouting effect is achieved in just one grouting, which significantly reduces material costs and construction periods.
Smart Images

Figure CN119707348A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building construction, and in particular to a shield synchronous grouting admixture, a shield synchronous grouting material and a preparation method thereof. Background Art
[0002] Shield tunnel construction is an advanced underground engineering method, in which synchronous grouting technology plays a vital role. Synchronous grouting means that during the tunneling process of the shield machine, after the assembly of the segments is completed, a suitable amount of slurry with good performance and certain early strength is injected into the gap between the segments and the soil through the synchronous grouting system to form a grouting layer. This process plays an indispensable role in ensuring the stability of the tunnel structure and controlling the deformation of the surrounding soil.
[0003] However, the existing shield synchronous grouting materials have a series of problems, including long initial setting time and too thin slurry consistency. These problems have brought many challenges to tunnel construction. Thin slurry will cause the shield synchronous grouting materials to be lost during the filling process, reduce the filling density, and thus affect the stability of the tunnel structure.
[0004] In the preparation of existing shield synchronous grouting materials, sodium-based bentonite is usually used to increase the consistency of the slurry, and the water absorption and expansion of sodium-based bentonite is used to solve the problem of too thin grouting consistency. However, in a water-rich environment, the existing shield synchronous grouting materials that only add sodium-based bentonite are found to have poor water dispersibility, which can easily lead to deformation, stratification or cracking of the grouting layer. Therefore, after the first synchronous grouting is completed, a secondary grouting will be carried out to consolidate the tunnel structure and improve the effect of synchronous grouting. However, the secondary grouting requires more slurry and takes a long time, which increases construction costs and prolongs the construction period. Summary of the invention
[0005] The purpose of the present invention is to provide a shield synchronous grouting material with high water-resistance dispersion to improve the filling capacity of the grout, thereby ensuring the stability of the tunnel structure and reducing the material cost of the project.
[0006] In order to achieve the above object, the present invention provides a shield synchronous grouting admixture, which comprises, by mass percentage:
[0007] Polycarboxylate water reducer 1%~2%,
[0008] Expansion agent 1%~2%,
[0009] Polyacrylamide 12%~18%,
[0010] Sodium silicate 15%~20%,
[0011] The balance is fly ash.
[0012] The present invention also provides a shield synchronous grouting material, comprising:
[0013] Slurry powder, the slurry powder is composed of 10% to 15% cement, 20% to 30% fly ash, and 40% to 60% machine-made sand, calculated by mass percentage;
[0014] The above-mentioned shield synchronous grouting admixture, the mass of the shield synchronous grouting admixture is 0.5% to 2% of the mass of the slurry powder;
[0015] Mixing water, the mass of the mixing water is 20% to 30% of the total mass of the slurry powder and the shield synchronous grouting admixture.
[0016] Furthermore, the cement is 42.5 ordinary Portland cement.
[0017] Furthermore, the fly ash is Class F Grade II fly ash.
[0018] Furthermore, the machine-made sand is quartzite machine-made sand.
[0019] Furthermore, the particle size of the machine-made sand is 1.6 mm to 2.2 mm.
[0020] Furthermore, the mixing water is tap water.
[0021] The present invention also provides a method for preparing the above-mentioned shield synchronous grouting material, comprising:
[0022] Step S1, mixing the cement, the fly ash and the machine-made sand for 10s to 30s to obtain the slurry powder;
[0023] Step S2, mixing the shield synchronous grouting admixture with the slurry powder obtained in step S1 for 10s to 30s to obtain a premixed shield synchronous grouting material;
[0024] Step S3, mixing the mixing water with the premixed shield synchronous grouting material obtained in step S2 for more than or equal to 200 seconds to obtain shield synchronous grouting material.
[0025] Compared with the prior art, the beneficial effects of the present invention include:
[0026] The shield synchronous grouting material provided by the present invention comprehensively optimizes the key properties of the shield synchronous grouting material, such as the initial setting time, water dispersibility, slurry consistency, and shrinkage. The present invention adopts the shield synchronous grouting admixture independently developed (hereinafter referred to as "grouting admixture") to replace the traditional bentonite. The grouting admixture includes polycarboxylic acid water reducer, polyacrylamide, sodium silicate, expansion agent, and fly ash. Through the synergistic effect of each component, the performance of the shield synchronous grouting material is comprehensively improved: the polycarboxylic acid water reducer reduces the water consumption and material cost under the premise of ensuring the fluidity of the slurry; the polyacrylamide aggregates the suspended matter into larger flocs through electrical neutralization and bridging adsorption, thereby enhancing the consistency and water dispersibility of the slurry; the sodium silicate forms a colloidal solution after dissolving in water, further increasing the consistency of the slurry; the expansion agent can generate a small expansion stress during the solidification process of the slurry to compensate for the shrinkage of the slurry; the fly ash acts as a medium filling to promote uniform mixing between the components.
[0027] Furthermore, the present invention further optimizes the water dispersibility and shrinkage of the shield synchronous grouting material by finely adjusting the ratio of the grouting admixture to cement, fly ash, machine-made sand, and mixing water. The test results show that the shield synchronous grouting material of the present invention achieves the expected secondary grouting effect with only one grouting, which significantly reduces the material cost of the project. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a comparison diagram of the water entry effect of the shield synchronous grouting material of Examples 1 to 3 of the present invention; wherein A represents Example 1, B represents Example 2, and C represents Example 3.
[0029] Figure 2 This is a core sample taken after one grouting of the shield synchronous grouting material of Example 2 of the present invention is completed. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In the description of the present invention, it should be noted that the terms "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0032] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0033] As used herein, the terms "slurry" and "paste" are used interchangeably.
[0034] The "concrete" mentioned in this article refers to the solidified body formed by the "shield synchronous grouting material" after solidification or hardening.
[0035] During synchronous grouting, shield synchronous grouting materials with high filling capacity should take into account the following performance balance: (1) High water resistance and dispersion: to ensure that in a water-rich environment, the slurry is not diluted by groundwater before solidification to ensure the grouting effect; (2) Appropriate consistency: Appropriate consistency to ensure that the slurry has a high density and thus has a high compressive strength; at the same time, ensure fluidity to ensure that the grouting process is efficient and smooth, so that the shield synchronous grouting material can penetrate into small gaps or pores; (3) Short initial setting time: Rapid solidification is conducive to preventing excessive loss of shield synchronous grouting materials during the solidification process and reducing the risk of slurry cracking; (4) Low shrinkage: to ensure that the solidified slurry is tightly combined with the surrounding soil.
[0036] However, as described in the background technology, the existing shield synchronous grouting materials have problems such as long initial setting time and too thin slurry consistency. Although adding sodium-based bentonite can improve the single performance of the slurry (improving the density of the slurry by increasing the consistency of the slurry), there is no shield synchronous grouting material on the market that can simultaneously take into account the comprehensive performance of suitable slurry consistency, high water resistance and dispersibility, short initial setting time, low shrinkage, etc. Therefore, in order to meet the construction requirements, secondary grouting is often required, which not only causes material waste, but also reduces construction efficiency.
[0037] To solve the above problems, the inventors independently developed a grouting admixture to replace the traditional bentonite, and optimized the ratio of the grouting admixture, slurry powder and mixing water, so that the shield synchronous grouting material can meet the construction requirements after one grouting, achieving the dual benefits of improving construction efficiency and reducing material waste.
[0038] The invention provides a grouting admixture for shield synchronous grouting material, which comprises, by mass percentage, 1%-2% of polycarboxylic acid water reducer, 1%-2% of expansion agent, 12%-18% of polyacrylamide, 15%-20% of sodium silicate, and the balance of fly ash.
[0039] Among them, the polycarboxylic acid water-reducing agent is a polycarboxylic acid high-efficiency water-reducing agent, provided by Suzhou Fuke Technology Co., Ltd.; the expansion agent is a plastic expansion agent, provided by Zhejiang Shuntai Rubber and Plastic Technology Co., Ltd.; the polyacrylamide is provided by Henan Saike Environmental Protection Technology Co., Ltd.; the sodium silicate is provided by Jiangsu Yubang New Materials Technology Co., Ltd.; the fly ash is Class F Grade II fly ash, provided by Rizhao Huaneng Power Plant.
[0040] The molecular structure of the polycarboxylic acid high-efficiency water-reducing agent contains hydrophilic groups such as carboxyl groups, which can form an adsorption layer on the surface of cement particles. Through steric hindrance and charge repulsion, the cement particles are dispersed, the aggregation and contact between particles are reduced, and the cohesion and viscosity of the slurry are reduced. In this way, the water consumption can be significantly reduced while maintaining the same fluidity. According to the test of GB / T 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", when the slump of concrete is maintained at 200mm, the concrete using the polycarboxylic acid high-efficiency water-reducing agent can achieve a water consumption reduction of more than 35% compared with the concrete not using the water-reducing agent, that is, the water reduction rate is greater than 35%, which helps to reduce material costs. The plastic expansion agent is an azodicarbonyl expansion agent. Azodicarbonyl can react with the cement hydration reaction product Ca(OH)2 to gradually release gases such as N2 and CO2, generate small expansion stress, and compensate for the volume shrinkage effect that generally occurs in the slurry during the hardening (solidification) process. The polyacrylamide has a good flocculation effect. During the hardening process of the slurry, the polyacrylamide aggregates the dispersed particles into larger floccules through electrical neutralization and bridging adsorption, thereby enhancing the consistency and water dispersibility of the slurry. The sodium silicate will form a colloidal solution after dissolving in water. This colloidal solution has a certain viscosity and consistency, which further increases the consistency of the slurry. The fly ash plays a role of medium filling to avoid uneven stirring caused by too small an amount of the grouting admixture when preparing the shield synchronous grouting material.
[0041] The grouting admixture for shield synchronous grouting material provided by the present invention achieves the optimal balance of the performance of shield synchronous grouting material by accurately controlling the proportion of each component. Specifically, the inventors found that if the content of the polycarboxylic acid high-efficiency water-reducing agent is less than 1%, the water-reducing effect is not good, and if it exceeds 2%, it may cause slurry segregation or excessive fluidity, affecting uniformity and strength. When the content of the plastic expansion agent is less than 1%, the expansion stress is insufficient, and if it is higher than 2%, it may cause excessive expansion and damage the structural stability. If the content of the polyacrylamide is less than 12%, the slurry consistency is insufficient and easy to disperse, and if it exceeds 18%, the slurry is too viscous, affecting the fluidity of the slurry. When the content of the sodium silicate is less than 15%, the slurry consistency is poor, and if it exceeds 20%, the slurry is too thick, which is not conducive to pumping.
[0042] The present invention also provides a shield synchronous grouting material, which adopts the above-mentioned grouting admixture and comprises, by mass percentage:
[0043] The slurry powder is composed of 10% to 15% cement, 20% to 30% fly ash, and 40% to 60% machine-made sand; the mass of the grouting admixture is 0.5% to 2% of the mass of the slurry powder; and the mass of the mixing water is 20% to 30% of the total mass of the slurry powder and the grouting admixture.
[0044] Among them, the cement is 42.5 ordinary Portland cement, provided by Shandong Shanshui Cement Group Co., Ltd.; the fly ash is Class F Grade II fly ash, provided by Rizhao Huaneng Power Plant; the machine-made sand is quartzite machine-made sand, the particle size of the quartzite machine-made sand is 1.6mm~2.2mm, provided by Qingdao Chengyang Graded Sand and Gravel Plant; the mixing water is tap water in the municipal pipeline.
[0045] The cement is the main cementitious material in the slurry powder, which forms a hardened body through hydration reaction, providing strength and structural stability for the slurry. The fly ash and the quartzite machine-made sand are used as admixtures and fine aggregates, respectively, to improve the density of concrete. The mixing water is the medium for mixing and flowing the shield synchronous slurry, so that the solid particles (such as cement, fly ash, machine-made sand, etc.) in the shield synchronous grouting material can be mixed evenly to form a uniform slurry, and at the same time provide fluidity so that the slurry can be pumped to the construction site. By adjusting the ratio of the grouting admixture to the cement, fly ash, and mixing water, the cement, fly ash, mixing water and the grouting admixture can work synergistically to jointly optimize the water dispersibility, slurry consistency, initial setting time and shrinkage of the shield synchronous grouting material.
[0046] The present invention also provides a method for preparing a shield synchronous grouting material, comprising:
[0047] Step S0, providing the above-mentioned measured cement, fly ash, machine-made sand, grouting admixture, and mixing water.
[0048] Step S1, mixing the cement, the fly ash and the machine-made sand for 10s to 30s to obtain the slurry powder. In some embodiments, the cement, the fly ash and the machine-made sand are mixed by using a high-speed mixer.
[0049] Step S2, mixing the grouting admixture with the slurry powder obtained in step S1 for 10s to 30s to obtain a premixed shield synchronous grouting material. In some embodiments, the slurry powder and the grouting admixture are stirred by using a high-speed mixer.
[0050] Step S3, mixing the mixing water with the premixed shield synchronous grouting material obtained in step S2 for more than or equal to 200 seconds to obtain shield synchronous grouting material. In some embodiments, the premixed shield synchronous grouting material and the mixing water are stirred by using a high-speed mixer.
[0051] The cement and grouting admixture react chemically when they meet water, and the content of the grouting admixture is less than that of the slurry powder. If the powder is mixed in water, the grouting admixture is easily consumed quickly, resulting in uneven distribution of the grouting admixture in the powder, which in turn leads to uneven consistency of the shield synchronous grouting material. Therefore, in the preparation method of the shield synchronous grouting material of the present invention, the powder is first dry-mixed, and then water is added for stirring, which effectively avoids the problem of rapid reaction of the grouting admixture, cement and water due to premature contact, ensures the uniform consistency of the shield synchronous grouting material, and improves the construction performance and final engineering quality of the shield synchronous grouting material. Furthermore, the powder is dry-mixed in two steps, which is conducive to a more uniform mixing of the grouting admixture with a lower content and the slurry powder.
[0052] In addition, considering that in actual construction, the powder mixing station is generally far away from the construction site, the powder is first evenly mixed (steps S1 and S2), and then water is added and stirred at the construction site (step S3) to form shield synchronous grouting material. This is conducive to ensuring that the premixed shield synchronous grouting material remains stable during transportation, and by accurately controlling the stirring time of step S3 at the construction site, it is ensured that the consistency of the shield synchronous grouting material meets the construction requirements.
[0053] The preparation method of the shield synchronous grouting material of the present invention is simple. It only needs to perform metering, mixing and stirring in sequence according to the above steps. By controlling the ratio and stirring time of each component, the shield synchronous grouting material with high water resistance, suitable slurry consistency, rapid solidification and low shrinkage can be obtained.
[0054] The specific implementation of the present invention is further described below in conjunction with examples and drawings.
[0055] Example 1
[0056] The method for preparing the shield synchronous grouting material provided in this embodiment comprises the following steps:
[0057] Step S101, weigh 15% of 42.5 ordinary Portland cement, 30% of Class F Grade II fly ash, and 55% of quartzite machine-made sand, respectively, in terms of mass percentage.
[0058] Step S201, weighing a grouting admixture having a mass of 0.5% of the total mass of the 42.5 ordinary Portland cement, Class F Grade II fly ash, and quartzite machine-made sand.
[0059] Step S301, weighing tap water whose mass is 30% of the total mass of the 42.5 ordinary Portland cement, Class F Grade II fly ash, quartzite machine-made sand, and the grouting admixture.
[0060] Step S401, putting the 42.5 ordinary Portland cement, Class F II fly ash, and quartzite machine-made sand into a mixer, mixing and stirring for 20 seconds to obtain a slurry powder.
[0061] Step S501, putting the slurry powder and the grouting admixture into a mixer, mixing and stirring for 20 seconds to obtain a premixed shield synchronous grouting material.
[0062] Step S601, mixing the premixed shield synchronous grouting material with the tap water for 300 seconds to obtain the shield synchronous grouting material.
[0063] Example 2
[0064] The difference between this embodiment and embodiment 1 is that in step S201, a grouting admixture having a mass of 1% of the total mass of the 42.5 ordinary Portland cement, Class F grade II fly ash, and quartzite machine-made sand is weighed.
[0065] Example 3
[0066] The difference between this embodiment and embodiment 1 is that in step S201, the grouting admixture is weighed with a mass of 1.5% of the total mass of the 42.5 ordinary Portland cement, Class F grade II fly ash, and quartzite machine-made sand.
[0067] The distribution ratios of the various components in the shield synchronous slurries prepared in Examples 1 to 3 are shown in Table 1 below.
[0068] Table 1: Mass percentage of each component in the shield synchronous slurry prepared in Examples 1 to 3
[0069]
[0070]
[0071] Among them, the mass percentage of the grouting admixture described in Table 1 refers to its percentage relative to the total mass of the slurry powder; the mass percentage of tap water described refers to its percentage relative to the total mass of the slurry powder and the grouting admixture.
[0072] Table 2: Test results of Examples 1 to 3
[0073] Example Water dispersion resistance Shrinkage Initial setting time 3d compressive strength 1 Easy to disperse underwater Micro expansion 8.5h 2.9Mpa 2 No dispersion underwater Micro expansion 8h 2.9Mpa 3 No dispersion underwater Micro-contraction 9h 2.9Mpa
[0074] Among them, the initial setting time refers to JGJ70-90 "Test Method for Basic Performance of Building Mortar", and is tested using a mortar setting time measuring instrument. The 3-day compressive strength (3d compressive strength) refers to JGJ70-90 "Test Method for Basic Performance of Building Mortar", and is tested using a pressure testing machine. The shrinkage test refers to JGJ70-90 "Test Method for Basic Performance of Building Mortar", and is tested using a vertical mortar shrinkage instrument.
[0075] The initial setting time of traditional shield synchronous grouting material is generally 10h~24h, and the 3d compressive strength is generally 0.70MPa~1.1MPa. It can be seen from the above Table 2 that the initial setting time of the shield synchronous grouting material prepared by using grouting admixtures instead of traditional bentonite is shorter, which meets the optimal construction requirements, proving that the shield synchronous grouting material of the present invention can solidify faster, so that the slurry is not easy to lose, ensuring the structural stability of the grouting layer, reducing the risk of cracking of the grouting layer, and thus helping to improve the filling capacity of the slurry. The 3-day compressive strength of the shield synchronous grouting material of the present invention is high, proving that the shield synchronous grouting material of the present invention has a high consistency and reaches a high density level, further proving the high filling capacity of the slurry.
[0076] It should be noted that the amount of grouting admixture added will also affect the performance of shield synchronous grouting material. For details, see Table 2 and Figure 1 , Figure 1 The dispersion of the shield synchronous grouting materials prepared in Examples 1 to 3 under water is shown; wherein, Figure 1 A in represents Example 1, Figure 1 B in represents Example 2, Figure 1 C in represents Example 3. Figure 1It can be clearly seen that the shield synchronous grouting material prepared in Example 1 is the easiest to disperse underwater, the shield synchronous grouting material prepared in Example 3 has the best anti-dispersion performance underwater, and the shield synchronous grouting material prepared in Example 2 is between the two. The high water resistance ensures the compactness of the shield synchronous grouting material in a water-rich environment and reduces the stratification rate of the grouting layer. From the test results of the shrinkage in Table 2, it can be seen that the shield synchronous grouting materials prepared in Example 1 and Example 2 are slightly expanded, while the shield synchronous grouting material prepared in Example 3 is slightly shrunk. In contrast, the micro-expansion stress generated by the micro-expanded shield synchronous grouting material during the solidification process helps to fill the gap in the shield tail building and reduce the quality defects such as the hollowing out and cracking of the tunnel vault caused by shrinkage deformation, thereby further improving the fillability of the grouting layer, while the micro-shrinking shield synchronous grouting material will produce volume shrinkage during the solidification process, which may affect the volume stability of the grouting layer and increase the risk of stratification and cracks. Therefore, in general, the shield synchronous grouting material prepared in Example 2 is the best shield synchronous grouting material among the three. It can be seen that the addition amount of appropriate grouting admixture is conducive to achieving the optimal balance between the underwater anti-dispersion, shrinkage, initial setting time and consistency of the shield synchronous grouting material, thereby ensuring that the grouting material can maintain good density during the construction process and remain stable in the underwater environment to prevent slurry loss.
[0077] Figure 2 This is a core sample diagram of the shield synchronous grouting material prepared in Example 2 after the first grouting is completed. In order to demonstrate, through core drilling detection on the shield synchronous grouting material prepared in Example 2 after solidification, it was found that when using a grouting admixture with a mass of 1% of the slurry powder mass, the density level of the first synchronous grouting can achieve the expected secondary grouting effect, thereby reducing the amount of secondary grouting slurry or even eliminating the secondary grouting, thereby reducing the process steps, significantly reducing the material cost of the project, and improving the efficiency and economy of construction.
[0078] In summary, the shield synchronous grouting material provided by the present invention achieves comprehensive optimization of the key performances of the shield synchronous grouting material by replacing traditional bentonite with a grouting admixture independently developed. The grouting admixture comprises a polycarboxylic acid water-reducing agent, an expansion agent, polyacrylamide, sodium silicate and fly ash. The synergistic effect of these components not only optimizes the consistency and shrinkage of the slurry, but also enhances the water dispersibility and reduces the initial setting time. The polycarboxylic acid water-reducing agent reduces the water consumption while maintaining fluidity, polyacrylamide enhances stability through flocculation, sodium silicate increases consistency, the expansion agent compensates for volume shrinkage, and fly ash promotes uniform mixing. By finely adjusting the ratio of the grouting admixture to cement, fly ash, machine-made sand and mixing water, the shield synchronous grouting material of the present invention can achieve the effect of traditional secondary grouting after one grouting, effectively reducing the material cost and improving the construction efficiency and economy.
[0079] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A shield synchronous grouting admixture, characterized in that: In terms of mass percentage, it includes: Polycarboxylate water reducer 1%~2%, Expansion agent 1%~2%, Polyacrylamide 12%~18%, Sodium silicate 15%~20%, The balance is fly ash.
2. A shield synchronous grouting material, characterized in that: include: Slurry powder, the slurry powder is composed of 10% to 15% cement, 20% to 30% fly ash, and 40% to 60% machine-made sand, calculated by mass percentage; The shield synchronous grouting admixture according to claim 1, wherein the mass of the shield synchronous grouting admixture is 0.5% to 2% of the mass of the slurry powder; Mixing water, the mass of the mixing water is 20% to 30% of the total mass of the slurry powder and the shield synchronous grouting admixture.
3. The shield synchronous grouting material according to claim 2, characterized in that: The cement is 42.5 ordinary Portland cement.
4. The shield synchronous grouting material according to claim 2, characterized in that: The fly ash is Class F Grade II fly ash.
5. The shield synchronous grouting material according to claim 2, characterized in that: The machine-made sand is quartzite machine-made sand.
6. The shield synchronous grouting material according to claim 5, characterized in that: The particle size of the machine-made sand is 1.6 mm to 2.2 mm.
7. The shield synchronous grouting material according to claim 2, characterized in that: The mixing water is tap water.
8. A method for preparing a shield synchronous grouting material as claimed in any one of claims 2 to 7, characterized in that: include: Step S1, mixing the cement, the fly ash and the machine-made sand for 10s to 30s to obtain the slurry powder; Step S2, mixing the shield synchronous grouting admixture with the slurry powder obtained in step S1 for 10s to 30s to obtain a premixed shield synchronous grouting material; Step S3, mixing the mixing water with the premixed shield synchronous grouting material obtained in step S2 for more than or equal to 200 seconds to obtain shield synchronous grouting material.
Citation Information
Cited By
Design method of high-performance grouting material accurately matched with physical property structure of soft coal rock
CN120954577A